Analisis Biaya Pemeliharaan Mesin Produksi Terhadap Hasil Produksi - Supiandi; Maman Setiawan (International Journal Administration, Business & Organization, 2020)
In printing company, the production process is often disrupted by the high amount of damage resulting in the expenditure for maintenance costs. The engines that are often damaged affects the printing products that will be produced. Due to the high amount of downtime, company profits will decrease because of the overrun of costs for maintenance. The problem raised in this study is whether the variable cost of engine maintenance with the corrective method and preventive method simultaneously and partially has a significant effect on increasing production results. Another problem that is raised is which variable has a relatively more dominant effect in increasing production results. The aim of this study is to analyze the engine maintenance cost with the methods already mentioned to increase production results. The results of the analysis show that partially, both corrective and preventive methods of engine maintenance cost have no effect in increasing production results. There is no dominant method. However, if both methods are done simultaneously, it will have a significant effect on the increase of production results.